P3.447 Leukocyte Extract Modulates Cellular Factors Involved in HIV Infection. (13th July 2013) - Fernandez-Ortega, C B; Casillas, D; Dubed, M; Navea, L; Ramirez, A C; Lopez, L; Paneque, T
Abstract : Background: Despite the therapeutic advances of antiretroviral, problems of drug resistance, latent viral reservoirs, and drug induced toxic effects that compromise effective viral control point to the need for new classes of anti-HIV drugs with different modes of action. An extract from human leukocyte called Dialyzable Leukocyte Extract (DLE) delays AIDS progression. However, the molecular bases supporting this effect are not completely comprehended. We hypothesises that active molecules from DLE modulate cellular factors involved in HIV infection. Methods: Using an in vitro infection model on MT4 cell line we demonstrated an inhibitory effect of DLE on HIV replication in treated cells which led us to identify molecules that could mediate this and other effects observed in this preparation. Results: DLE shows a significant inhibitory effect on HIV replication ranged from 80–90% according to the viral challenge. In addition, DLE shows modulation of important endogenous factors involved in HIV immunopathogenesis like TNFalpha and transcription factors NFkB and Sp1. Conclusions: DLE effect on cellular factors involved in HIV replication correlates with DLE inhibitory effect on HIV in vitro replication. The inhibition of HIV replication observed with DLE treatment could be mediated by TNF and transcriptions factors modulation involved in HIV infection. These finding could support the use of DLE on HIV patients and/or in health individuals to prevent the infection.